URGENSI LEARNING RESOURCES (SUMBER BELAJAR) DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - Samsinar S. (Didaktika : Jurnal Kependidikan, 2019)
Learning as a process of interaction between educators, students, and learning resources. In learning, educators must make themselves a source of learning and prepare and design other learning resources including media or media or multimedia as support in learning to improve the quality of learning. The quality of learning is determined by educators. Educators must have creativity and productivity in managing learning resources strting from planning learning resources, using learning resources and evaluating learning resources. In planning learning resources, educators must determine and choose learning resources that are appropriate to the learning objectives, characteristics of students, and the situation and conditions of the school. In terms of using learning resources, educators must be able and skilled in designing and utilizing learning resources in learning, and in terms of evaluating learning resources, educators must be able to assess appropriate learning resources, which provide more benefits and assess learning resources that have advantages and limitations in learning certain things.Keywords: learning resources, quality of learning